Preparation and Characterization of Large Area Li-NASICON Electrolyte Thick Films - Ricardo Jiménez; Isabel Sobrados; Sandra Martínez-Chaparro; Angel Adolfo del Campo; M. Lourdes Calzada; Jesús Sanz; Shu Yi Tsai; Ming Rui Lin; Kuan Zong Fung; Edvardas Kazakevicius; Algimantas Kežionis (Inorganics, 2019)
The preparation of solid electrolyte ceramic membranes is the object of intense study for its fundamental parts in the development of all solid-state batteries and improved battery separators. In this work, the procurement of large area solid electrolyte ceramic thick film membranes of the Li-NASICON Li1.3Al0.3Ti1.7(PO4)3 (LATP) composition is attempted. Through the use of LATP powders from a sol−gel reaction, a slurry is formulated and tape casted. The green tapes are sintered using two sintering times. In both cases, ceramic thick films of a 5.5 × 5.5 cm2 area and ≈250 µm average thickness were obtained. The characterization indicated almost pure phase samples with a bi-modal microstructure composed of large and smaller grains, being larger for longer sintering time. The samples are porous and brittle, presenting very high “bulk” conductivity but lower total direct current (DC) one, as compared with the commercial Li-NASICON (OHARA) thick films with a similar area. The larger the grains, the poorer the total conductivity and the mechanical properties of the thick-films. The formation of poorly adhering grain boundaries as the grain size grows is responsible for the worsened properties. A better control of the microstructure is mandatory.